A Value-Based Decision-Making Model for Selecting Sustainable Materials for Buildings - Ruslan, A.A.B. (Insight Society, 2021)
Nowadays, the earth faces problems and challenges from different circumstances due to the dramatic rise of urban modernization. The construction industry is the most contributor to climate change. Achieving sustainability in construction is complicated, but one of the most optimal strategies is selecting building materials with a lower carbon footprint. Therefore, this research aims to investigate the criteria for sustainable materials selection, rank and prioritize sustainable criteria, and developing value-based decision making. A mixed method was used to satisfy the objectives through an extensive literature review, surveys, and interviews with experts. The statistical descriptive was based on a scatter plot of mean and standard deviation, AHP judgment and Value-based decision-making using function over cost. There are two alternatives obtained in this study: Aluminum Composite Panel (ACP) and Stainless Steel. As a result, the suitable alternative for sustainable faÃ§ade material is ACP based on value-based calculation. The tendency of choosing sustainable material depends on the stakeholders, owner of the building, designers, and others. The research is to show the way in selecting sustainable material by using value-based analysis. This study could expect to give feasibility and useful knowledge in solving problems and increase the use of sustainable materials in building construction. Future research may be conducted with different requirements for sustainable materials. AHP and Value-based analysis are structured technique that solves a complex problem easily using mathematics and psychology approach. Â© 2021. All Rights Reserved.